Production and Characterization of Cellulase Enzyme Produced by Bacillus Isolates from Different Sources - Elkhalil , Elhadi A. I.; Gaffar, Fatima Y. (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted to produce and characterize cellulase enzymes from Bacillus isolates and to determine the optimum conditions for cellulase activity. Four Bacillus isolates were used: iso 9+ from compost and iso13, iso23 and iso20 from soil. The four isolates (9+, 23, 13 and 20) gave average cellulase activities of 2.89, 3.12, 3.48 and 3.53 Unit/ml, respectively. The pH optimum for cellulases from the four isolates was 6, and the temperature optima were 45, 60, 60 and 80°C, respectively. Cellulases from isolates 13 and 23 were more thermostable and retained 40.2% and 21.9% of their initial activities after incubation for 110 min at 90°C. Cellulase was produced under solid state fermentation conditions in maize cobs, sorghum stover or bagasse pretreated with 2% hydrochloric acid from the above four isolates as well as from two more isolates (iso4- and iso2-) which were isolated from cow dung. Maximum cellulase activity was 3.78 Unit/ml from isolate 4- using bagasse and maize cobs as substrate. These results demonstrated that Bacillus isolates 13, 23, 20 and 9+ produced active thermostable extracellular cellulase. Bagasse and maize cobs are suitable as substraes for production of the enzyme cellulase under solid state fermentation.